Managerial Abilities of Women Headed Households - K. Uma Rani; G.Bhaskar (Journal of Agricultural Extension Management, 2025)
This study attempts to understand the profile of women headed households and the relationship between personal variables and managerial abilities of Jann women. A sample of 270 women headed households were drawn for the study covering Telangana, Rayalseema and Coastal region of Andhra Pradesh. The study reveals that education, self-confidence and participation of women in SHGs and extension activities have significant positive relation with managerial efficiency. The study recommends that women headed households should be given priority in extension activities ·of ongoing schemes for providing them opportunities to sharpen their managerial skills. Special management modules could be developed for training these women which will enhance their self-confidence and managerial abilities and help them become more productive. Extension programmes with a combination of rational and creative approach to problem solving and decision making will have potential for providing a conceptual framework, upon which the programmes can be based for developing the managerial efficiency of these women headed households, say the authors